1985
DOI: 10.1029/jb090ib08p06695
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and geochemistry of a sediment‐hosted hydrothermal sulfide deposit from the Southern Trough of Guaymas Basin, Gulf of California

Abstract: Samples dredged from a 15‐m‐high hydrothermal mound atop the flat turbidite pond in the Southern Trough of Guaymas Basin consist of pyrrhotite‐rich massive sulfide, barite, barite + calcite, talc, and opaline silica as well as substrate material composed of fossiliferous, clay‐rich ooze. An 11‐m‐long sediment core taken near the dredge site shows increasing hydrothermal alteration with depth; anhydrite‐filled fractures near the base of the core appear to be channels for hydrothermal discharge. Oxidation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
1
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(47 citation statements)
references
References 49 publications
3
42
1
1
Order By: Relevance
“…3). A single value of 21.5‰ for the sulfate sample at the EHF falls within the overall range of sulfate samples from other seafloor hydrothermal fields (from 19 to 25‰; n = 288) (data are from Shanks and Niemitz, 1982;Kerridge et al, 1983;Zierenberg et al, 1984Zierenberg et al, , 1993Koski et al, 1985;Shanks and Seyfried, 1987;Hannington and Scott, 1988;Shanks, 1988, 1994;Kusakabe et al, 1990;Blum and Puchelt, 1991;Iizasa et al, 1992;Peter and Shanks, 1992;Lein et al, 1993;Chiba et al, 1998;Gemmell and Sharpe, 1998;Herzig et al, 1998a, b;Knott et al, 1998;Marumo and Hattori, 1999;Zeng et al, 2002a, b;de Ronde et al, 2003;Kim et al, 2004;. Sulfide minerals from the EPR near 1-2°S have much higher sulfur isotope ratios (pyrite δ 34 S values from 3.0 to 5.8‰, avg.…”
Section: Sulfur Isotopic Compositions In Sulfidesmentioning
confidence: 99%
“…3). A single value of 21.5‰ for the sulfate sample at the EHF falls within the overall range of sulfate samples from other seafloor hydrothermal fields (from 19 to 25‰; n = 288) (data are from Shanks and Niemitz, 1982;Kerridge et al, 1983;Zierenberg et al, 1984Zierenberg et al, , 1993Koski et al, 1985;Shanks and Seyfried, 1987;Hannington and Scott, 1988;Shanks, 1988, 1994;Kusakabe et al, 1990;Blum and Puchelt, 1991;Iizasa et al, 1992;Peter and Shanks, 1992;Lein et al, 1993;Chiba et al, 1998;Gemmell and Sharpe, 1998;Herzig et al, 1998a, b;Knott et al, 1998;Marumo and Hattori, 1999;Zeng et al, 2002a, b;de Ronde et al, 2003;Kim et al, 2004;. Sulfide minerals from the EPR near 1-2°S have much higher sulfur isotope ratios (pyrite δ 34 S values from 3.0 to 5.8‰, avg.…”
Section: Sulfur Isotopic Compositions In Sulfidesmentioning
confidence: 99%
“…The formation of such deposits can be attributed to several abiogenic processes: sedimentation from hydrothermal plumes (e.g., Barrett et al 1987;Mills, Elderfield, and Thomson 1993); in situ precipitation from diffuse low-temperature flow through sediments (e.g., Koski et al 1985;Alt 1988), typically 20-100…”
Section: Introductionmentioning
confidence: 99%
“…These temperatures are unusually low for hydrothermal talc (Lonsdale et al 1980;Koski et al 1985;Styrt et al 1981;Zierenberg and Shanks 1983) and lower than those estimated for chloritites sampled at comparable depths. A possible explanation is that talc-rich rocks equilibrated with an 18 O-enriched hydrothermal fluid, e.g.…”
mentioning
confidence: 90%
“…McLeod and Stanton 1984;Aggarwal and Nesbitt 1984;Costa et al 1983;Koski et al 1985;Kranidiotis and MacLean 1987;Lonsdale et al 1980;Shau and Peacor 1992;Goodfellow and Franklin 1993;Zierenberg et al 1995) and distinct populations characterized by either moderately (FeO £ 4 wt%) or highly ferroan compositions may occur at the same site. Available estimates of the temperatures of formation of hydrothermal talc are in the range 270-420°C (Lonsdale et al 1980;Koski et al 1985;Styrt et al 1981;Zierenberg and Shanks 1983), therefore usually higher than those reported for Mg-rich saponite.…”
Section: Talcmentioning
confidence: 99%
See 1 more Smart Citation